On the circulation response to climatic forcing - Baker, H (2019)
Climate change is expected to cause changes in the general atmospheric circulation. Particularly important to the global population is an understanding of how weather and climate will change. North Atlantic jet stream changes will drive weather and climate changes, primarily over North-Western Europe, but also over North America, Asia and other parts of the globe. This makes it vital to understand how climate change will affect the jets to determine how the weather and climate will respond. However, the exact nature of the climate change forcings affecting the jet are uncertain. Here, sensitivity studies using a hierarchy of models to determine possible circulation changes due to the thermal forcing of the atmosphere are performed. It is found that the location of forcing, both its latitude-longitude position and its height, has a profound effect on how the circulation responds. A simple mechanistic understanding for shifts and strengthening of the jet through changes in the mean meridional temperature gradients is presented, along with mechanisms for how Hadley circulation changes can affect the jet, and for how tropically forced waves affect the Northern Hemisphere circulation. Important differences between the responses in winter and summer are observed, which can lead to seasonally dependent extreme temperature and precipitation responses. Key forcing locations that force the atmospheric circulation effectively are highlighted. In these locations, the uncertainties in how the forcing due to climate change will manifest must be reduced so that the circulation response can be better quantified. An important uncertainty is how the atmosphere heats up compared to how sea surface temperatures change and connected to this, how the land-sea temperature contrast will respond. As these uncertainties are reduced, the results from these sensitivity studies will provide a guide to understanding how the circulation will change and the associated impacts of the changes.